Perceived stress and life satisfaction among university students: the mediating and moderating roles of coping strategies and personality traits - Elsayed, Hala Abd Ellatif (Frontiers in Psychology, 2025)
IntroductionThe transition to university is often accompanied by significant stress, which can adversely affect students’ life satisfaction. This study aimed to investigate the relationship between perceived stress and life satisfaction among university students, with a focus on the mediating role of coping strategies and the moderating role of personality traits.MethodsA cross-sectional survey was conducted with 520 university students (M = 21.5 years, SD = 2.3). Participants completed validated measures including the Perceived Stress Scale (PSS), Satisfaction with Life Scale (SWLS), Brief COPE Inventory, and Big Five Inventory-2 (BFI-2). Data were analyzed using PROCESS macro regression modeling (Models 4 and 1).ResultsPerceived stress showed a significant nonlinear (cubic) association with life satisfaction (R2 = 0.263, p < 0.001). Overall, higher stress was consistently linked to lower life satisfaction, with scores declining from low to high stress levels (e.g., SWLS = 26.4 at −1 SD; SWLS = 24.8 at mean; SWLS = 21.9 at +1 SD). Moderation analyses revealed that Agreeableness (β = −0.0486, p < 0.001), Conscientiousness (β = −0.0436, p < 0.001), and Openness (β = −0.0538, p < 0.001) significantly moderated this association, whereas Extraversion and Negative Emotionality were nonsignificant. Mediation analyses further indicated that adaptive coping partially buffered the negative impact of stress (β = 0.22, p < 0.01), while maladaptive coping exacerbated it (β = −0.29, p < 0.001).DiscussionThese findings underscore the importance of cultivating adaptive coping mechanisms and tailoring stress management interventions to students’ individual personality profiles. Such strategies may enhance students’ well-being and academic success.